1978
DOI: 10.1002/1097-0142(197810)42:4<1793::aid-cncr2820420418>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The significance of intracytoplasmic proteins in Reed-Sternberg cells

Abstract: Lymphoid tissue of 42 patients with Hodgkin's disease was studied with immunohistological techniques on the light microscopic and ultrastructural level. The presence of IgG in some Reed‐Sternberg (R‐S) cells was confirmed, and in addition serial sections and a double staining technique revealed that these cells also contained both kappa and lambda light chains. Furthermore two serum proteins, human serum albumin and alpha‐1‐antitrypsin, were demonstrated in the same positive R‐S cells. The ultrastructural loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

1980
1980
1997
1997

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 26 publications
0
17
0
4
Order By: Relevance
“…Other immunoglobulins, albumin, a1AT and oflACT, have also been found within RS cells'0 [15][16][17] but reports of their incidence vary widely and little attention has been paid to their staining pattern or cytoplasmic distribution. In this study we have shown that II serum proteins other than IgG can be demonstrated in RS cells but that, contrary to other reports,17 their incidence and staining pattern differ from IgG and they are thus thought to represent a different phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other immunoglobulins, albumin, a1AT and oflACT, have also been found within RS cells'0 [15][16][17] but reports of their incidence vary widely and little attention has been paid to their staining pattern or cytoplasmic distribution. In this study we have shown that II serum proteins other than IgG can be demonstrated in RS cells but that, contrary to other reports,17 their incidence and staining pattern differ from IgG and they are thus thought to represent a different phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…This distribution has been interpreted as indicating both specific ribosomal synthesis18 19 and nonspecific leakage into the cell. '7 Other serum proteins have been found in RS cells but less commonly than IgG [15][16][17] In the light of the conflicting interpretations as to the extent and significance of IgG and other proteins in RS cells we have performed an immunoperoxidase study of 12 different serum proteins including IgG, on a series of biopsies from patients with Hodgkin's disease. We have stained for J chain which although associated extracellularly only with dimeric IgA and 19 S IgM is synthesised in cells producing immunoglobulin of all classes.…”
mentioning
confidence: 99%
“…Warm slides to RT (1 hr) if incubated at 4OC. 6. Wash for 10 min with 1% NGS (for polyclonal antibodies) or 1% NRS (for monoclonal antibodies) in TBS.…”
Section: Block Endogenous Peroxidase Activity By Incubatingmentioning
confidence: 99%
“…This technique is widely used for visualizing different cell populations in which neither population contains both antigens (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Most examples of two distinct antigens demonstrating within the same cell have utilized immunofluorescence with multiple fluorescent markers or immunofluorescence in combination with immunoenzymatic labeling (17,(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…The finding of immunoglobulins, both within (Garvin et at., 1974: Taylor, 1974, 1976Payne et al, 1976) and on the surface (Kadin et al, 1974;Boecker et al, 1975) (Garvin et al, 1974;Taylor, 1974Taylor, , 1976Kadin et al, 1978;Poppema et al, 1978). Certainly the mere presence of immunoglobulin, without evidence of endogenous synthesis, does not identify a cell as a B lymphocyte.…”
Section: Lymphoblasticmentioning
confidence: 99%